Dependence of the short-wavelength cutoff in the mid-IR pulse spectrum on the interaction length in SiO2 and CaF2. (November 2020) - Geints, I Yu; Zaloznaya, E D; Kompanets, V O; Dormidonov, A E; Chekalin, S V; Kandidov, V P
Abstract: This paper presents the results of experimental and numerical study of the anti-Stokes wing formation and the evolution of the short-wavelength cutoff in the 1900 nm pulse spectrum during its propagation and filamentation in fused silica and calcium fluoride. It is found that during the light bullet formation the short-wavelength cutoff in the supercontinuum spectrum is shifted to the anti-Stokes region with an increase in the nonlinear optical interaction length with the medium. However, change in the short-wavelength cutoff in the formed light bullet spectrum throughout its further propagation is insignificant.